Evaluation of an intervention to improve waterless surgical hand antisepsis accuracy in a tertiary hospital of East China: a prospective pre-post intervention study - Ma, Yonghui; Yue, Xia; Li, Ning; Wang, Jixia; Wang, Juan; Xia, Yujie; Zhang, Xing; Zhang, Min; Wang, Peng; Wang, Shuangshuang; Wen, Luhan; Liu, Zhenghui; et al. (Frontiers in Public Health, 2025)
BackgroundSurgical site infections (SSIs) are the most frequent type of healthcare-associated infections (HAIs) in low- and middle-income countries (LMICs). Effective surgical hand antisepsis is a critical step in the prevention of SSIs. Limited research on clinician interventions regarding accuracy in waterless surgical hand antisepsis (WSHA) is available. This study evaluated the effect of a tailored, multifaceted improvement strategy on WSHA in a tertiary hospital in East China. We also performed a process evaluation to explore the mechanisms through which our strategy brought about change.MethodsA prospective, pre-post intervention study was performed from January 2024 through December in 28 departments. Data from the pre-post intervention studies were collected using a specially designed score checklist and video surveillance (≥4 per department). In addition to the score collection, the mid-term assessment also used a questionnaire that included demographic characteristics and cultural climate surveys. A number of customized interventions were conducted before and after the mid-term assessment.ResultsThe scores of pre-intervention, mid-term assessment, and post-intervention were 71.4 ± 16.8, 92.7 ± 9.2, and 78.7 ± 19.4, respectively. There were statistical differences between the scores of pre-intervention and mid-term assessment (p < 0.001), mid-term assessment and post-intervention (p < 0.001), and pre-intervention and post-intervention (p = 0.002). There were statistical differences among different genders, ages, positions, years of working experience, and departments (p < 0.05). Lower scores appeared in males, orthopedics, and internal medicine. The psychological comfort score was more than 4 points when being reminded to standard WSHA. The number of times the score was less than 2 points was reduced.ConclusionOur interventions have been successful in improving WSHA accuracy. In the future, it will be necessary to closely monitor and supervise WSHA practices to determine the long-term effectiveness of current intervention strategies.